La marge au coeur du milieu urbain : un premier terrain dans deux favelas paulistanas. - Blanche Panchot (Confins)
The first fieldwork experience is always particular, it finally allows us to put on practice on our own the methodology learned at the university. This field chronicle thus resumes the major steps of my work in two favelas of São-Paulo. The events described below served as a « bottom up » analysis of a peculiar relationship between the city and areas considered as marginal. I have also tried to understand how the municipality organizes these territories, either by its lack of action or, conversely, by the construction of enclaving infrastructures.